IMPACT OF METRO BUS SYSTEM ON FEMALE MOBILITY IN ISLAMABAD-RAWALPINDI - Wajid Ali; Tayyeba Khalil (International Journal of Contemporary Issues in Social Sciences, 2023)
This study explores the role of public transport system in female mobility in Pakistan. Based on a micro-study, using a mix method approach, this research assesses the impact of the Metro Bus System (MBS) on female mobility in the twin cities of Islamabad-Rawalpindi. Primary data is collected from three groups of female passengers – working women, students, and casual travelers. The findings of this study suggest that the metro bus service in Islamabad-Rawalpindi has improved the service quality of public transportation for female passengers. Despite some limitations it can be concluded that the MBS has effectively addressed issues such as uncertainty and insecurity for female passengers to a great extent. Running feeder buses at link routes, extension of metro bus to the busiest routes interim of daily commuters flow and running female exclusive buses during peak hours can further improve service quality.